CONCEPT OF MUSLIM PERSONALITY ACCORDING TO MUHAMMAD ALI AL-HASYIMI - Yusnaili Budianti; Salminawati Salminawati; Hanifa Azmi (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This study aims to describe the concept of Muslim personality according to Muhammad Ali Al-Hashimi in the book Syakhshiyatul Muslim Kamaa Yashughuhal Islam Filkitab Wa Sunnah. Furthermore, this study aims to describe the thoughts of Muhammad Ali Al-Hasyimi about the Muslim personality and its application in daily life and find the relevance of Muhammad Ali Al-Hasyimi's thoughts about the Muslim personality with the reality of education in Indonesia at this time.This type of research is Library Research using a character study approach. The primary data source is Syakhshiyatul Muslim Kamaa Yashughuhal Islam Filkitab Wa Sunnah book. At the same time, the secondary data sources are translation books, as well as books about the personality of Muslims. To analyze the data in this study using content analysis. This activity began by using descriptive, interpretative, and comparative analysis methods. The findings in this study are, first, the Muslim personality is a personality who practices the teachings of Islam in kaffah (thorough) following the Qur'an and Sunnah, namely being a humanist. Second, the Muslim personality application, according to Ali Al-Hashimi, is grouped into nine sections, namely, (1) Muslims against his Lord, (2) Muslims against himself, (3) Muslims against his parents, (4) Muslims against his wife, (5) Muslim against his children, (6) Muslim against family, (7) Muslims against their neighbors, (8) Muslims against their friends, and (9) Muslims against their communities. Third, the concept of Muslim personality, according to Muhammad Ali Al-Hasyimi, is relevant to the Indonesian education system in law No. 20 of 2003 on the definition and purpose of education, as well as curriculum 2013 and Presidential Regulation of the Republic of Indonesia number 87 of 2017 on strengthening Character Education.